Oat, Wheat, and Sorghum Genotype Reactions to Meloidogyne incognita and Meloidogyne javanica - Brida, Andressa Lima de [UNESP]; Souza da Silva Correia, Erika Cristina [UNESP]; Castro e Castro, Barbara Monteiro de; Zanuncio, Jose Cola; Siciliano Wilcken, Silvia Renata [UNESP] (Soc Nematologists, 2017)
Meloidogyne spp. are the most economically important species of plant-pathogenic nematodes. Plant resistance and crop rotation are the main nematode management methods. Thus, the objective was to evaluate the resistance of seven wheat genotypes, five oat genotypes, ten sorghum hybrids, and three sorghum-sudangrass genotypes to Meloidogyne incognita and Meloidogyne javanica. The crops were sowed in pots with an autoclaved substrate. A single plant/pot was left after thinning. The soil was infested with 5,000 eggs of the studied nematodes. Tomato (cv. Rutgers) plants were used as the standard for nematode susceptibility. The evaluations were conducted 60 d after inoculation. Gall and egg-mass indexes were obtained according to a 0-5 scale. Plants with a reproduction factor higher than 1.0 were classified as susceptible (S) and lower than 1.0 as resistant (R). Wheat and oat genotypes did not allow M. incognita and M. javanica reproduction, proving resistance to these organisms. Sorghum genotypes had different reactions to M. incognita and M. javanica. The tomato (cv. Rutgers) plants demonstrated the viability of the nematode inoculum for the three crops. The wheat and oat genotypes and the sorghum hybrids 'BRS-610', 'BRS-800', and '307.343' can be used in crop rotation systems for M. incognita and M. javanica management.
Keywords: crop rotation; management; resistance; root-knot nematodes